Online absention System as implementation of ASN management in the new normal era in Jambi Province - Asti Harkeni; Novia Susianti (Yayasan Ilomata, 2020)
Since the issuance of Presidential Decree (Keppres) No. 11 of 2020 concerning the Establishment of Public Health Emergency COVID-19 and Circular Letter of the National Personnel Agency (BKN) Number 11/SE/IV/2020 concerning the Guidelines for Disciplinary Punishment for State Civil Apparatus (ASN) Conducting Travel Activities Outside the Region and/or Going Home during the Emergency Public Health Period, Jambi Provincial Government implements an online attendance policy through the SiAbOn application installed on a smartphone. The goal is to monitor the location of the presence of the ASN during the Eid al-Fitr holidays from 23 to 25 May 2020, as well as concrete efforts to stop the spread of COVID-19. The research problem formulation is to see how the effectiveness and efficiency as well as the impact of the SiAbOn application on the implementation of ASN management in the new normal era. Data sources were obtained from ASN, Department of Communication and Information (Dinas Kominfo), and Jambi Province Regional Personnel Agency (BKD Prov. Jambi). The sample location is Jambi Province. The research method used was quantitative. The results showed that out of 11,214 ASNs, 92.37% (10,351 ASNs) used SiAbOn, while 7.70% (863 ASNs) did not. These results are very satisfying considering the preparation time until the implementation was very short, only 14 days with an ASN area of more than 600 km2, geographical challenges, and limited internet infrastructure. The SiAbOn implementation policy during the Eid holiday then was adopted as a permanent policy in the new normal era replacing the obligation to record attendance using a hand-key machine which could be the source of COVID-19 spread.